Assessment of Wet Wipes and their Environmental Significance – A Review Article - Dwivedi, Bhaskar C; Chakraborty , Ayan (International Research Journal of Ayurveda & Yoga, 2024)
Nowadays, wet wipes are highly common in the cosmetics market. Also called moist tissues. Its primary function is cleaning. It is a fantastic substitute for traveling with water, soap, and a towel. Wipes are currently a non-woven material with a rapidly rising market. The wipes have a tendency to retain liquid and gather to hold debris, dust, and other cleared particles. Preservatives, water, surfactants, buffers, fragrances, and nutritious components are all combined to make wet wipes. The major disadvantage of wet wipes they are made of synthetic fiber are non biodegradables which lead to microplastic pollution and harsh impact on the human skin, so get ride off these situations wet wipes industry should have to use herbal finished and eco-friendly fibers to make wet wipes for day to-day use. The present paper aims to throw a light on the assessment of the environmental significance of wet wipes.